P-020 Emergent Carotid Artery Stenting with or without Intracranial Tandem Occlusion Lesions Following Carotid Endarterectomy. (26th July 2014) - Vargas, J; Zuckerman, S; Chaudry, I; Turner, R; Turk, A; Spiotta, A
Abstract : Introduction: Stroke in the immediate post-operative period following carotid endarterectomy (CEA) is usually due to carotid thrombosis. Many centers have begun incorporating angiography before re-exploration, which has the advantage of confirming carotid occlusion and treating tandem intracranial lesions. The aim of this study is to determine the safety and efficacy of this strategy. Methods: A retrospective review was performed of all cases undergoing stenting of the carotid artery following carotid endarterectomy from November 2009 to February 2014 at the Medical University of South Carolina and the Vanderbilt University Medical center. Charts and angiographic images were reviewed. Six cases of carotid thrombosis within 72 h of CEA and subsequent stent reconstruction are summarised. Results: Five patients had greater than 70% carotid stenosis prior to carotid endarterectomy. One patient had intraoperative occlusion and dissection of the ICA which was noted on intraoperative carotid duplex ultrasound. All patients underwent post-operative computer tomography (CT) or computer tomography perfusion (CTP) scans with subsequent cerebral angiography and stent reconstruction within 11 h of symptom onset. Two patients had tandem middle cerebral artery M3 branch occlusion which was successfully recanalised. In all cases, recanalization was successfully completed between 40 to 160 min. There were no procedural complications. Conclusion: Emergent endovascular evaluation in the setting of acute post CEA thrombosis is a safe and timely treatment option, with the benefit of detecting and treating embolic intracranial lesions. More investigation is necessary to define the role of immediate angiography and intervention in this rare surgical complication. Disclosures: J. Vargas: None. S. Zuckerman: None. I. Chaudry: 2; C; EV3/Coviden, Microvention, Penumbra, Stryker, Pulsar, Blockade, Medina. R. Turner: 2; C; Coviden, Microvention, Blockade, Codman, Stryker, Reverse Medical, Pulsar Vascular, Siemens, Penumbra. A. Turk: 1; C; Stryker, Codman, Microvention, Penumbra, Siemens, Coviden. 2; C; Stryker, Microvention, Penumbra, Pulsar Vascular. 4; C; Pulsar Vascular, Lazarus Effect, Medina, Blockade. A. Spiotta: 2; C; Pulsar Vascular, Microvention, Penumbra.